A New Swarm Intelligence Approach for Optimal Chiller Loading for Energy Conservation - M. H., Sulaiman; Hassan, Ibrahim; Hamdan, Daniyal; Mohd Rusllim, Mohamed (Elsevier, 2014)

(untitled)
This paper employs a recent swarm intelligence technique to solve optimal chiller loading (OCL) problem, namely differential search (DS) algorithm. In general, significant energy savings can be obtained by optimizing chiller operation and design in heating, ventilation and air-conditioning (HVAC) systems. In this paper, partial load ratio (PLR) of the chiller is used as parameters to be optimized where the power consumption in kW is used as objective function to be minimized. In order to show the effectiveness of the proposed technique, the comparison with other techniques has been done and analyzed.